Updating the knowledge of sand flies (Diptera, Psychodidae) in Rondônia State, Brazil - Pereira Júnior, Antonio Marques (2022)
Fundação Oswaldo Cruz. Fiocruz Rondônia. Porto Velho, RO, Brasil / Fundação Oswaldo Cruz. Fiocruz Rondônia. Instituto Nacional de Ciência e Tecnologia de Epidemiologia da Amazônia Ocidental. Porto Velho, RO, Brasil.